A Benefits Approach to Certain Accounting Policy Choices. - Carter, William K. (The Accounting Review, 1981)
Abstract ABSTRACT: This paper is concerned with the existence of some accounting choices that can be examined to determine which of two reporting alternatives is preferable in terms of gross potential user benefits, without knowing statement users' preferences for information. It is also noted that many policy choices in accounting are not subject to this analysis. At a minimum, the identification of which of these two categories fits a particular accounting policy decision should indicate that the attention of policy-making bodies could be most usefully directed to the costs of policy choices in certain cases. Possible explanations for the continuing focus on benefits rather than costs of alternatives are examined.